Duality of Custom Villages and Service Villages In Tengangan Pegringsingan - Agus Sumahendra; I Wayan Sukayasa; Ni Wayan Karmini (Green Publisher Indonesia, 2022)
Indonesia is a people-sovereign constitutional state and is a unitary state in the form of a republic. As a rule-of-law country, Indonesia must comply with the concept of a rule-of-law state in general in the world, namely as a country based on a constitution, adhering to democratic principles, recognizing and protecting human rights, as well an independent and impartial judiciary. The purpose of this study was to determine the duality of traditional villages and official villages in Tenganan Peringsingan. This research is field research with a research concentration namely the Duality of Government of Traditional Villages and Service Villages in Tenganan Pegringsingan. First, there are four reasons for the duality of governance of traditional villages and official villages in Tenganan Peringsingan. (1). Social Development Modernization Factors Society must be able to adapt to developments that occur as a result of modernity. efforts to maintain the cultural and religious purity of the Tenganan Peringsingan Traditional Village